Crystalline structure and polymorphism in powders and thin films of dibenzotetraaza[14]annulene - Udovitskiy, V.G. (Журнал физики и инженерии поверхности, 2016)
The increasing interest in dibenzotetraaza[14]annulene (TAA) is motivated by the demonstrated perspectives for using this organic semiconductor in actively progressive now spintronics and in other fields of electronics. This work is the first study on polymorphism, which may occur in powder and in thin TAA films. The results of this study showed that the initial TAA powder synthesized by chemical methods are both now known polymorphic forms of TAA which were registered at Cambridge Crystallographic Data Centre as GAGVAL and GAGVAL01. It was also found that at the condensation of thin films G-form initially formed while after increasing the film thickness the G01-form will forms also and a continuous films have twophases and contain both known polymorphs — G and G01. The X-ray diffraction pattern indicated also that crystallites in thin TAA films show a strong preffered orientation (texture) with the (100) plane (for G-polymorph) and (002) plane (for G01-polymorph) parallel to the surface of the substrate Увеличение интереса к дибензотетрааза[14]аннулену (ТАА) обусловлено перспективами использования этого органического полупроводника в активно развивающейся сейчас спинтронике, а также и в других областях электроники. Данная работа является первым исследованием, касающимся полиморфизма, который может иметь место в кристаллах ТАА как в порошкообразном виде, так и в его тонких пленках. Установлено, что в порошкообразном веществе ТАА, синтезированном химическими методами, присутствовали обе известные полиморфные формы ТАА, зарегистрированные в Кембриджском центре кристаллоструктурных данных под шифрами GAGVAL и GAGVAL01 (G и G01). Обнаружено, что при конденсации тонких пленок ТАА вначале преимущественно образуются кристаллиты G-формы. По мере увеличения толщины пленки образуется и G01-форма, а сплошная пленка является двухфазной, т. е. содержит оба известных полиморфа. Рентгенодифракционным методом установлено, что пленки ТАА обладали преимущественной ориентацией кристаллитов (текстурой) плоскостью (100), параллельной подложке для G-формы, и, соответственно, плоскостью (002) для G01-формы. Зростання інтересу до дибензотетрааза[14]анулену (ТАА) обумовлено перспективами використання цього органічного напівпровідника в спінтроніці, яка зараз активно розвивається, а також і в інших областях електроніки. Ця робота є першим дослідженням, що стосується поліморфізму, який може мати місце в кристалах ТАА як в порошкоподібному стані, так і в його тонких плівках. Виявлено, що в порошкоподібній речовині ТАА, синтезованій хімічними методами, були присутні обидві відомі поліморфні форми ТАА, зареєстровані в Кембриджському центрі кристалоструктурних даних під шифрами GAGVAL та GAGVAL01 (G і G01). Встановлено, що при конденсації тонких плівок ТАА спочатку переважно утворюються кристаліти G-форми. Зі зростанням товщини плівки утворюється також і G01-форма, а суцільна плівка є двохфазною, тобто містить обидва відомі поліморфи. Рентгенодифракційним методом встановлено, що плівки ТАА мали переважну орієнтацію кристалітів (текстуру) площиною (100), паралельною до підкладки для G-форми, і, відповідно, площиною (002) для G01-форми.